CRISPR-Cas System: An Approach With Potentials for COVID-19 Diagnosis and Therapeutics - Kumar, Prashant; Malik, Yashpal Singh; Ganesh, Balasubramanian; Rahangdale, Somnath; Saurabh, Sharad; Natesan, Senthilkumar; Srivastava, Ashish; Sharun, Khan; Yatoo, Mohd. Iqbal; Tiwari, Ruchi; Singh, Raj Kumar; Dhama, Kuldeep (Frontiers in Cellular and Infection Microbiology, 2020)
COVID-19, the human coronavirus disease caused by SARS-CoV-2, was reported for the first time in Wuhan, China in late 2019. COVID-19 has no preventive vaccine or proven standard pharmacological treatment, and consequently, the outbreak swiftly became a pandemic affecting more than 215 countries around the world. For the diagnosis of COVID-19, the only reliable diagnostics is a qPCR assay. Among other diagnostic tools, the CRISPR-Cas system is being investigated for rapid and specific diagnosis of COVID-19. The CRISPR-Cas-based methods diagnose SARS-CoV-2 infections within an hour. Apart from its diagnostic ability, the CRISPR-Cas system is also being assessed for antiviral therapy development; however, to date, no CRISPR-based therapy has been approved for human use. The Prophylactic Antiviral CRISPR in huMAN cells (PAC-MAN), which is a Cas 13 based strategy, has been developed against coronavirus. Although this strategy has the potential to be developed as a therapeutic modality, it may face significant challenges for approval in human clinical trials. This review is focused on describing the potential use and challenges of CRISPR-Cas based approaches for the development of rapid and accurate diagnostic technique and/or a possible therapeutic alternative for combating COVID-19. The assessment of potential risks associated with the use of CRISPR will be important for future clinical advancements.